Clinical experiences with robotic computed tomography-guided interventions: A comparison with manual technique - Ashwin Kumar A,; Sivakumar Kannappan,; Geetha G, (Asian Journal of Medical Sciences, 2025)
Background: Image-guided biopsies have become standard practice; however, challenges such as multiple punctures and re-attempts can complicate procedures. The introduction of robotic guidance systems, such as MAXIO offers a potential solution for improving planning and navigation. This study evaluated the efficacy of the MAXIO needle-guiding robotic device in computed tomography (CT)-guided interventions compared with conventional manual techniques. Aims and Objectives: This study aimed to evaluate the performance of the MAXIO robotic system for CT-guided biopsies at the Barnard Institute of Radiology and compare it with the conventional manual technique. Materials and Methods: A total of sixty patients who underwent CT-guided biopsies were retrospectively divided into two groups: Group A (manual procedure) and Group B (robot-assisted procedure). The MAXIO device was utilized in combination with a Siemens 32-slice CT scanner for robot-assisted biopsies. Key parameters analyzed between the two groups included the volume CT dose index, dose-length product (DLP), target location, target depth, target size, distance from the entry point, needle angulation, procedural time, number of punctures, complications, and re-biopsy rates. Results: Significant differences were found between the two groups in the number of punctures (p = 0.002), DLP (p = 0.0001), and degree of needle angulation (p = 0.0002), with the robotic technique demonstrating a better performance. Although the procedural time was reduced in the robotic group, this difference was not statistically significant (p = 0.104). Other assessed parameters, such as complications and rebiopsy rates, showed no significant differences. Conclusion: Robotic-assisted CT-guided procedures using the MAXIO system showed improved diagnostic accuracy and safety, with reductions in radiation dose, needle manipulations, and punctures, compared to conventional manual techniques.